Application of vertical electrical sounding (VES) for groundwater exploration in Onitsha and environs, Nigeria - Osele, Chika; Onwuemesi, Ajana; Anakwuba, Emmanuel; Chinwuko, Augustine (International Journal of Advanced Geosciences, 2016)
Surface geo-electrical survey using vertical electrical sounding (VES) method has been carried out in Onitsha and environs in southwestern part of Anambra state in order to determine the aquifer characteristics and groundwater potential of the area. Eleven vertical electrical soundings were carried out within the area of study using schlumberger array configuration. The interpretation of the vertical electrical sounding (VES) data revealed three to five geoelectric units with depth to the aquiferous layers ranging from 21 to 78m and resistivity of the saturated layers varying between 20 and 5600 ohm-m. Aquifer characteristics such as transmissivity and hydraulic conductivity calculated from interpretated VES result ranged from 2.55m2/day to 29.01m2/day and 0.03m/day to 1.37m/day respectively. This result shows that the water saturated sandstone units of the study area is hydrological good and capable of producing optimum groundwater yield. Furthermore, borehole could be drilled at depth between 40 and 110m in the area for sustainable water supply and hydrochemical study carried out to determine the water quality for domestics and municipal purposes.